Cultivating Identity, Sowing Relationships, Fertilizing Success, and Harvesting Coexistence: Understanding Oklahoma Producer Identity and Relationships - Audrey E. H. King; Quisto Settle (Journal of Applied Communications, 2021)
The USDA has identified coexistence, or producers growing food in a variety of ways (conventionally, organic, etc.) in a harmonious manner as a critical challenge and high priority. Despite this call for coexistence and assurance of mutual success, agricultural sectors often have conflicts. Both sides of the niche and mainstream rift tend to pick and choose radical examples of problematic practices to portray the opposition. Producers, more so than most other occupations, have a deeply entrenched occupational identity. Many studies focused on the need for relationships between agricultural producers and the public. No work has been found to understand how producers from different sectors of agriculture view one another. This study sought to understand producers’ identities and the relationships producers have with one another. Results indicate the occupation of farming, family ties, connection and duty to the land, hard work and pride defines producers’ identities. When defining a “good farmer,” producers cited innovation and efficiency, farm succession, passion and joy, and profits as markers of success. The relationships between producers varied. Overall, producers respected other producers enough to make their own choices concerning production. Social media was often mentioned when producers talked about how they communicate with one another.
Keywords: qualitative interviews; social identity; producer relationships